Case sensitive? A review of the literature on the use of case method in entrepreneurship research. Issue 3 (5th May 2015) - David Higgins, Professor Kiran Trehan; Professor Pauric McGowan, Dr; Henry, Colette; Foss, Lene
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to review the use of case method in entrepreneurship research, and to identify trends in its current application. A key objective of the paper is to lay the foundation for a future research agenda by critically reviewing relevant literatures and offering insights into the use of case method in particular settings. The paper also helps identify areas where case method could add value to research findings in future scholarship. Design/methodology/approach – Using a Boolean search, a systematic literature review (SLR) was undertaken across the "big five" entrepreneurship journals in the five-year period between 2008 and 2012. The search initially yielded a total of 269 "hits". Following exclusion criteria, the list was refined to a total of 52 empirical papers, and these were reviewed using a comprehensive reading guide developed by the authors. Findings – The paper finds that relatively few articles published in the "big five" entrepreneurship journals use case method, despite repeated calls in the literature for more in-depth, qualitative approaches. This potentially suggests that case method is not fully accepted as a legitimate or sufficiently rigorous approach in the upper echelons of contemporary published entrepreneurship scholarship. Overall the paper argues for greater acceptance of the use of case method amongst the academic community, alongside greater confidence in its application. This can be achieved by learning from other disciplines where the case approach is more established. Research limitations/implications – While a comprehensive SLR was undertaken, the search was restricted to a limited time period and across a limited number of top tier journals. Practical implications – The paper highlights incidents where case method has been used successfully, identifies gaps in the literature and contributes towards setting a future research agenda that should be of particular value to qualitative researchers. Originality/value – The paper builds on extant literatures by furthering our understanding of the use of case method in entrepreneurship research. It should be of value to qualitative scholars applying case method in their empirical work, as well as those seeking to extend their methodological reach beyond a purely quantitative orientation.